The Impact of Isha Yoga Practices on Mental and Physical Well-being: A Narrative Synthesis of Current Literature. - Giridharan, Selvaraj; Soumian, Soni; Pandiyan, Bhuvana (International Research Journal of Ayurveda & Yoga, 2024)
Isha Yoga is a comprehensive approach that integrates yogic practices such as Isha Kriya, Shambhavi Mahamudra, Upa Yoga, and the Samyama program. These practices have garnered attention for their potential health benefits including stress reduction, emotional equilibrium, and enhanced physical well-being. This review aimed to evaluate the impact of Isha Yoga on physical and mental health outcomes by analysing evidence from randomised controlled trials (RCTs), observational studies, and survey-based research. Methods:A comprehensive literature search was conducted across multiple academic databases, including studies published between 1990 and 2024. The inclusion criteria were Studies investigating the effects of Isha Yoga on mental health, physical health, and quality of life were included. Eligible studies were categorised as RCTs, observational studies, or survey based studies. Quality assessments were performed using established tools, including the Cochrane Risk of Bias Tool for RCTs, the Newcastle-Ottawa Scale (NOS) for observational studies, and CHERRIES for survey studies. Results:Seventeen studies were included in the review, comprising three RCTs, 11 observational studies, and three surveys. Evidence from high-quality RCTs suggests that Isha Yoga practices significantly reduce stress, anxiety, and depression, while enhancing mental well-being. Observational studies and surveys have reported improvements in cardiovascular health, metabolic markers, and the overall quality of life. However, the strength of the evidence varies: the most robust findings relate to mental health outcomes, whereas physical health benefits rely on moderate-quality observational evidence. Conclusion: Isha Yoga demonstrates promising benefits for both mental and physical health, particularly in reducing stress and anxiety, and improving emotional well-being. However, further high-quality research is necessary to corroborate these effects and investigate underlying mechanisms, such as autonomic regulation and neuroplasticity. Future studies should explore the long-term impacts of these practices and their potential role in holistic health strategies to promote sustainable well-being.